Sustainable transition from fossil fuel to geothermal energy: a multi-level perspective approach - Widya yudha, Satya; Tjahjono, Benny; Longhurst, Philip J. (MDPI, 2022)
Indonesia is currently undergoing the energy transition from heavily fossil fuel-dependent energy to cleaner sources of energy in order to achieve its net-zero emissions by 2060. In addition to reducing fossil fuel dependency, as one of the countries with the most geothermal reserves, the optimization of geothermal energy in Indonesia could be key to facilitating the energy transition. The objective of this paper is to elaborate on the transition process, which incorporates the destabilization of fossil fuel and the growth of geothermal energy, by analyzing the impact of both exogenous and endogenous factors on the supply chain structures of both sectors. This study employs workshop involving geothermal stakeholders in Indonesia, combined with the application of the Multi-Level Perspective (MLP) framework as the theoretical lens. The study found that energy demand, environmental awareness, energy regulations, energy supply chain, and geothermal potential breakthroughs are important aspects pertinent to the MLP components, namely the socio-technical landscape, socio-technical regime and niche innovations. The socio-technical landscapes are exogenous factors that pressurize the energy sector regime allowing the niche innovation, in the form of geothermal innovation, to penetrate the fossil fuel regime, allowing it to transition to a geothermal regime. The transition pathways include several measures that could break down the fossil fuel and build up geothermal energy, through a number of schemes and incentives.
Keywords: energy transition; geothermal energy; multi-level perspective; supply chain; sustainability